EmojiHeroVR: A Virtual Reality Game for Collecting Partially Occluded Emotional Faces - Ortmann, Thorben; Hulsemann, Mirco; Wang, Qi; Putzar, Larissa (2024 12th International Conference on Affective Computing and Intelligent Interaction Workshops and Demos (ACIIW), 2024)
We present EmojiHeroVR, a Virtual Reality (VR) high-score game in which players reenact facial expressions to earn points. It provides an engaging method to collect emotional faces partially occluded by Head-Mounted Displays (HMDs), thereby promoting Facial Expression Recognition (FER) in VR settings. Developed using the Unity3D game engine, EmojiHeroVR integrates face detection and FER models via the Unity Sentis package. Results from a study with 37 participants who completed the Game Experience Questionnaire (GEQ) and Virtual Reality Sickness Questionnaire (VRSQ) indicate that EmojiHeroVR is an effective tool for data collection and offers an engaging experience for players.